Cultural Da'wah in the Sambas Malay Community through Tepung Tawar Tradition - Lamazi, Lamazi; Amin, Muliaty; Ali, Baharuddin; Yaumi, Muhammad; Masduki, Anwar (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
Sambas Malay community is included in an area with a tradition of spreading da'wah, one of which is the tradition of tepung tawar (fresh flour). The spread of da'wah through this tradition is a contact of customs and culture and is not in line with Islamic teachings. Hence, the tradition of fresh flour is one part of the cultural da'wah in the Sambas Malay community. This study aims to examine the value of da'wah contained in the tradition of tepung tawar (fresh flour) in the life of the Sambas Malay community. This research is descriptive field research using qualitative analysis. Data collection was done through observation, interview and documentation. The results of this study found that the form of cultural da'wah contained in the tradition of tepung tawar (fresh flour) in the Sambas Malay community consists of three stages: preparation, implementation, and post-implementation. There are several values contained in this tradition of fresh flour such as having an open attitude, having high Islamic values, ethical and moral values, togetherness values, shared ideals, deliberation values, and socio-cultural values and religiosity values. As well as the relationship between the tradition of tepung tawar (fresh flour) with aqiqah, which is in contact with Hinduism, Buddhism and Islam, this becomes a style of tradition that exists in the life of the Sambas Malay community, which is seen in the tradition of tepung tawar (fresh flour)